PLANNING THE AUDIT OF ESTIMATED LIABILITIES IN ACCORDANCE WITH INTERNATIONAL STANDARDS - M. A. Shtefan (Финансы: теория и практика)
The transfer of the Russian audit procedures to international auditing standards (IAS) makes it important to identify the main differences between national and international standards. The need to adjust to new rules of in-house audit standards regulating the processes of audit planning, audit evidence collection, preparation of working documents is becoming more urgent. The paper discusses the audit planning methodology for one of the most risky items in financial reporting - the balance sheet item “estimated liabilities” - prone to the risk of gross misstatement due to the lack of strict regulation of estimated liabilities valuation and criteria for their recognition and the use of professional judgment of financial experts in this process. The paper contains a number of recommendations for each stage of audit planning, namely, setting goals and objectives for the estimated liabilities audit, assessing the risk of material misstatement and inherent risk using the author’s methodology for assessing the in-house control system performance, calculation of the materiality of distortions in financial reporting information, and audit sampling. The materials of the paper are based on the requirements of international financial reporting standards and international audit standards and can be used by practicing auditors in the course of external and internal audits as well as by accountants, students and university lecturers.